Faktor-Faktor Penyebab Kemenangan OK Arya Zulkarnain dalam Pilkada Kab. Batu Bara - YURIAL ARIEF LUBIS (Politeia: Jurnal Ilmu Politik, 2016)
This Reseach based on the case of personal candidates OK. Arya Zulkarnain and Gong Matua Siregar who wont he local elections in the District of Batu Bara in 2008. Theelection of personal candidates to be the Regentand Vice Regent in the District of Batu Bara, is the first victory in thelocal election sat the district level in Indonesia. Personal candidates OK. Arya and Gong Siregar managed to win from the other spouse, particularly the candidate promoted by political parties. The results showed that, there are 2 (two) dominant factors causing personal candidatewins OK. Arya and Gong Siregar. Two dominant factor sare, among others, the first Factors figure OK. Arya as a fighter who makes the blossoming district.Andsecond, organizational factors GEMKARA as a substitute for a political party winning machine. On the other hand the victory of personal candidates OK. Arya and Gong Siregar shows that there are problemsin the recruitment patternand the winning party's machine politics. This research method is qualitative and the data collection techniques performed by the method of interviews. Keywords: Personal candidates, Local elections, political party.